ORGANIZATIONAL BEHAVIOR AS A FRAMEWORK FOR BIBLIOMETRIC RESEARCH ON THE LINKS BETWEEN WORKLOAD, CULTURE, AND DISCIPLINE IN THE WORKPLACE AND EFFICIENCY - Haryawan, Beny; Sopiah, Sopiah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Workload, organizational culture, work discipline, and job performance are some of the topics that this bibliometric review hopes to go into. The study finds trends, patterns, and gaps in the existing literature by using bibliometric analytic approaches. It utilizes co-citation and keyword analysis to uncover patterns of research collaboration and creates a publishing map according to year, author, journal, institution, and country. Researchers, practitioners, and policymakers can benefit from the analysis by better understanding the most recent breakthroughs and trends in organizational behavior, specifically related to employee performance. Furthermore, it addresses voids in the existing literature and pinpoints topics that require additional research. The results can help improve organizational policy initiatives and direct future research in the fields of human resource management and organizational behaviour. Job interview phrases and corporate culture were the subjects of an online poll that ran from 2019 through 2024. Beyond highlighting three ways these approaches could be enhanced to increase data quality, the research tries to demonstrate the benefits of online testing beyond its convenience. These recommendations for enhancing the quality of data can be applied to online organizational surveys and experiments.